2010
DOI: 10.1016/j.ydbio.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Paneth and goblet cell homeostasis and increased endoplasmic reticulum stress in Agr2−/− mice

Abstract: Anterior Gradient 2 (AGR2) is a protein disulfide isomerase that plays important roles in diverse processes in multiple cell lineages as a developmental regulator, survival factor and susceptibility gene for inflammatory bowel disease. Here, we show using germline and inducible Agr2−/− mice that Agr2 plays important roles in intestinal homeostasis. Agr2−/− intestine has decreased goblet cell Mucin 2, dramatic expansion of the Paneth cell compartment, abnormal Paneth cell localization, elevated endoplasmic reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
230
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(243 citation statements)
references
References 31 publications
(53 reference statements)
11
230
1
1
Order By: Relevance
“…The AGR2 protein contains a canonical cleavable N-�������l ��g��l ������� ���� ���g��� �� �� ��� ��c������ pathway (21). The secreted proteins metastasis-associated GPI-anchored C4.4A protein and the extracellular domain �� α-dystroglycan, have been reported to directly interact ���� AGR2, ����c����g ��������l ��c������� ��� AGR2 in the promotion of tumor metastasis via the regulation of ��c����� �������� ��� ��� ������c���� ���� ��� �����c�ll�l�� matrix (17,22). Thus, AGR2 interacts with the cell surface in ����� �� ����l��� �������� ��� ������� ����� c�ll ���������-tion.…”
Section: Discussionmentioning
confidence: 99%
“…The AGR2 protein contains a canonical cleavable N-�������l ��g��l ������� ���� ���g��� �� �� ��� ��c������ pathway (21). The secreted proteins metastasis-associated GPI-anchored C4.4A protein and the extracellular domain �� α-dystroglycan, have been reported to directly interact ���� AGR2, ����c����g ��������l ��c������� ��� AGR2 in the promotion of tumor metastasis via the regulation of ��c����� �������� ��� ��� ������c���� ���� ��� �����c�ll�l�� matrix (17,22). Thus, AGR2 interacts with the cell surface in ����� �� ����l��� �������� ��� ������� ����� c�ll ���������-tion.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with a mutation in the endoplasmic reticulum stress response key regulator XBP1 are more susceptible to induced colitis (28), but how this affects Muc2 has not been studied. The Agr2 protein, which has a special thioredoxin-like domain, is essential for the in vivo production of Muc2, and Agr2-null mice are highly susceptible to colitis (29,30). Finally, it has also been observed that several mouse strains with mutations causing a dysfunctional Muc2 mucin show a strong unfolded response (31).…”
Section: Structure Of Muc2 Mucinmentioning
confidence: 99%
“…Fittingly, hypomorphic XBP1 variants confer genetic risk for both forms of IBD, Crohn's disease and ulcerative colitis (Kaser et al, 2008). Additional genetic risk factors that impact the UPR have been discovered in IBD (e.g., ORMDL3 [McGovern et al, 2010] and AGR2 [Zheng et al, 2006]), and in some cases their genetic deletion in mice can lead to spontaneous IBD-like disease as well (Zhao et al, 2010). Notably, it appears that IECs in IBD generally experience unresolved ER stress, even in the absence of overt tissue-destructive inflammation (Heazlewood et al, 2008;Kaser et al, 2008;Tréton et al, 2011), with the effectiveness of the UPR being under the influence of primary (genetic) and secondary (environmental) factors (Kaser and Blumberg, 2011).…”
mentioning
confidence: 99%